Research motivation as a mediating variable between system intelligence, academic grit, and academic achievement among postgraduate students, faculty of education, Zagazig University - Marwa Hamdy Helal; ElSayed Abohashem Hassan (BMC Psychology)
Abstract Background Recent years have witnessed a revolutionary transformation in information technology, characterized by the proliferation of electronic information platforms, with the Egyptian Knowledge Bank being a notable example. Understanding how to effectively navigate these complex systems requires investigation into key factors, particularly system intelligence. Objectives This study aimed to examine the mediating role of research motivation in the relationship between system intelligence, Academic Grit, and Academic Achievement. Method Using a correlational design, the study surveyed 600 post-graduate students aged 25–55 years (M = 33.22, SD = 8.09) through online snowball sampling. Data were collected using the Research Motivation Scale, System Intelligence Scale, Academic Grit Scale, and Grade Point Average (GPA). Statistical analyses were conducted using IBM Amos, Spss 23. Results Path analysis revealed that system intelligence had an indirect effect on Academic Grit through research motivation. Additionally, direct effects were observed from system intelligence to research motivation, system intelligence to Academic Grit, and Academic Grit to Academic Achievement. Conclusions This study highlights research motivation as a crucial mediator in the relationship between system intelligence, academic grit, and academic achievement. The findings suggest potential interventions to enhance academic achievement by fostering system intelligence and academic grit through the development of research motivation.